A transition metal sulfide / carbon composite negative electrode material, and a preparation method and use thereof
Patent Information
- Application Number
- CN202310578811.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-22
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-05-22
AI Technical Summary
尽管MOFs具有上述优势,但由于不可避免的结构损坏,MOFs衍生的材料仍然表现出较差的结构稳定性以及较低的电子导电率
[0057]本发明首先将过渡金属有机框架材料在高温热解条件下生成镶嵌有过渡金属纳米颗粒的氮掺杂的多孔无定形碳骨架,并其将作为核芯材料,然后在核芯表面负载过渡金属盐,该过渡金属盐形成包覆层结构,且该过渡金属盐在氢气气氛下能够形成过渡金属纳米颗粒包覆层,该过渡金属纳米颗粒包覆层作为催化剂,在有机碳源的作用下,在过渡金属纳米颗粒层表面生成纳米导电碳层,最后高温下部分过渡金属纳米颗粒与硫粉反应生成过渡金属硫化物纳米颗粒。
Smart Images

Figure BDA0004241043320000111
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of lithium-ion battery anode materials, specifically relating to a transition metal sulfide / carbon composite anode material, its preparation method, and its applications. Background Technology
[0002] With the increasing demand for electrochemical storage devices, lithium-ion batteries have been widely used in the consumer market due to their significant energy density and excellent cycle performance. Carbon materials, as anode materials, exhibit good reversible capacity and cycle life in lithium-ion batteries, but their energy density is limited by their relatively low theoretical specific capacity. For example, the capacity of currently commercially available graphite anode materials is approaching its theoretical limit, making it difficult to meet the ever-growing demand for high energy density. To address future market demands, the development of anode materials with high specific capacity has become an urgent priority.
[0003] Among many high-performance anode materials, transition metal sulfides (such as CoS2) stand out due to their high theoretical specific capacity (870 mAh·g). -1 Transition metal sulfides (TMS) have attracted considerable attention due to their low cost. However, they still have some shortcomings in practical applications, such as large volume changes during cycling and easy pulverization. Numerous studies have proposed various strategies to improve these problems, such as introducing carbon materials to buffer the volume changes of electrode materials during charge and discharge and to adsorb polysulfides. Metal-organic frameworks (MOFs), as porous inorganic-organic hybrid materials, have attracted widespread attention due to their high porosity, large specific surface area, and structural diversity. Benefiting from these advantages and compositional characteristics, MOFs are considered ideal precursors for the preparation of transition metal sulfides. Existing techniques use porous Co-MOF precursors to synthesize nitrogen-doped hollow carbon spheres embedded with CoS2 nanoparticles. Benefiting from the hollow structure and the suppression of CoS2 volume expansion by the nitrogen-doped carbon framework, this material exhibits excellent lithium storage performance. Despite these advantages, MOF-derived materials still exhibit poor structural stability and low electronic conductivity due to unavoidable structural damage. Summary of the Invention
[0004] To address the problems existing in the prior art, this invention provides a transition metal sulfide / carbon composite anode material, its preparation method, and its applications. The composite anode material comprises transition metal nanoparticles, transition metal sulfide nanoparticles, conductive carbon nanoparticles, and nitrogen-doped porous amorphous carbon. The composite anode material can withstand the stress generated by the volume change of the transition metal sulfide, constraining and buffering the volume change of the transition metal sulfide, reducing the volume expansion factor of the transition metal sulfide after cyclic charge-discharge, and further preventing the pulverization of the composite anode material; simultaneously, it can also improve the conductivity and electrochemical performance of the composite anode material.
[0005] The objective of this invention is achieved through the following technical solution:
[0006] A method for preparing a transition metal sulfide / carbon composite anode material, the method comprising the following steps:
[0007] (1) The transition metal-organic framework material was heat-treated under an inert atmosphere to prepare precursor 1;
[0008] (2) The precursor 1 from step (1) is mixed with an aqueous solution of a transition metal salt and stirred to prepare precursor 2;
[0009] (3) The precursor 2 from step (2) is heat-treated under the protection of hydrogen and an inert atmosphere, and then an organic carbon source is introduced to continue the heat treatment to prepare the precursor 3.
[0010] (4) The precursor 3 from step (3) is mixed with sulfur powder and heat-treated under an inert atmosphere to prepare the transition metal sulfide / carbon composite anode material.
[0011] According to an embodiment of the present invention, in step (1), the transition metal-organic framework material is prepared by the following method: mixing a transition metal salt, an organic ligand and an organic solvent, reacting them, and preparing the transition metal-organic framework material.
[0012] In a preferred embodiment, the transition metal salt is selected from at least one of chromium salts, iron salts, cobalt salts, nickel salts, and copper salts. Preferably, the transition metal is selected from at least one of chromium nitrate, iron nitrate, cobalt nitrate, nickel nitrate, and copper nitrate.
[0013] In a preferred embodiment, the organic ligand is selected from at least one of naphthalenetetracarboxylic anhydride, dimethylimidazole, 2,5-dihydroxyterephthalic acid, pyromellitic acid, and terephthalic acid.
[0014] In a preferred embodiment, the organic solvent is selected from at least one of methanol, ethanol, formaldehyde, acetaldehyde, DMF, and water.
[0015] In a preferred embodiment, the mass ratio of the transition metal salt to the organic ligand is 1:(2-4), for example, 1:2, 1:3 or 1:4.
[0016] In a preferred embodiment, the sum of the masses of the transition metal salt and the organic ligand, and the volume ratio of the organic solvent, is (0.01–0.1) g:1 mL, for example, 0.01 g:1 mL, 0.02 g:1 mL, 0.03 g:1 mL, 0.04 g:1 mL, 0.05 g:1 mL, 0.06 g:1 mL, 0.08 g:1 mL, 0.09 g:1 mL, or 0.1 g:1 mL.
[0017] In a preferred embodiment, the reaction is carried out under stirring conditions.
[0018] In a preferred embodiment, the reaction time is 6 to 12 hours, and the reaction temperature is room temperature.
[0019] In a preferred embodiment, the reaction further includes post-processing steps such as centrifugal washing and vacuum drying. Preferably, the vacuum drying temperature is 60–100°C.
[0020] According to an embodiment of the present invention, in step (1), the temperature of the heat treatment is 700–900°C, such as 700°C, 750°C, 800°C, 850°C, or 900°C. The heating rate is 2–10°C / min. The heat treatment time is more than 1 hour, for example, 1–3 hours, such as 1 hour, 2 hours, or 3 hours. The inert atmosphere is, for example, nitrogen, helium, argon, etc.
[0021] According to an embodiment of the present invention, in step (1), the transition metal-organic framework material generates transition metal nanoparticles (Cr, Fe, Co, Ni or Cu) and nitrogen-doped porous amorphous carbon skeleton during high-temperature pyrolysis, and the transition metal nanoparticles are uniformly distributed on the porous amorphous carbon skeleton; that is, the obtained precursor 1 has a nitrogen-doped porous amorphous carbon skeleton structure, and the nitrogen-doped porous amorphous carbon skeleton is also embedded with transition metal nanoparticles.
[0022] According to an embodiment of the present invention, in step (2), the mass ratio of the transition metal salt to the precursor 1 is 1:(10-20), for example, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19 or 1:20.
[0023] According to an embodiment of the present invention, in step (2), the concentration of the transition metal salt in the aqueous solution of the transition metal salt is 2-5 g / L, for example, 2 g / L, 3 g / L, 4 g / L or 5 g / L.
[0024] According to an embodiment of the present invention, in step (2), the mixing temperature is room temperature, and the mixing time is not specifically defined, as long as the loading of transition metal salts can be achieved.
[0025] According to an embodiment of the present invention, in step (2), the transition metal salt is selected from at least one of chromium salts, iron salts, cobalt salts, nickel salts, and copper salts. Preferably, the transition metal is selected from at least one of chromium nitrate, iron nitrate, cobalt nitrate, nickel nitrate, and copper nitrate.
[0026] According to an embodiment of the present invention, step (2) further includes post-processing steps such as centrifugal washing and vacuum drying after the stirring is completed. Preferably, the temperature of the vacuum drying is 60-100°C.
[0027] According to an embodiment of the present invention, in step (2), in the mixed system, the transition metal salt can be loaded onto the surface of the precursor 1 to form a coating layer structure, thereby obtaining the precursor 2. The transition metal salt loaded onto the surface of the precursor 1 can form a coating layer structure, which can be converted into a transition metal nanoparticle coating layer under the action of hydrogen gas. This transition metal nanoparticle coating layer can catalyze the formation of nano-conductive carbon from an organic carbon source.
[0028] According to an embodiment of the present invention, in step (2), the mass of the transition metal salt loaded on each gram of precursor 1 is 20-60 mg, for example 20 mg, 30 mg, 40 mg, 50 mg or 60 mg.
[0029] According to an embodiment of the present invention, in step (3), the volume ratio of hydrogen to inert atmosphere is 1:(1-3), for example, 1:1, 1:2 or 1:3.
[0030] According to an embodiment of the present invention, in step (3), the temperature of the heat treatment is 700–900°C, such as 700°C, 750°C, 800°C, 850°C, or 900°C. The heating rate is 2–10°C / min. The inert atmosphere is, for example, nitrogen, helium, argon, etc.
[0031] According to an embodiment of the present invention, step (3) specifically includes the following steps:
[0032] Precursor 2 from step (2) was heated to 700–900°C for 1–3 hours under the protection of hydrogen and an inert atmosphere. Then, an organic carbon source was introduced and kept at the temperature for 1–5 hours. After cooling to room temperature, precursor 3 was obtained.
[0033] According to an embodiment of the present invention, in step (3), the organic carbon source is selected from one or more of acetylene, ethylene, methane, ethane, propane and n-butane.
[0034] According to an embodiment of the present invention, in step (3), the volume ratio of the organic carbon source to the inert atmosphere is 1:(2-15), for example, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14 or 1:15.
[0035] According to an embodiment of the present invention, in step (3), an organic carbon source is introduced into each gram of precursor 2 at a rate of 3 to 5 mL / min.
[0036] According to an embodiment of the present invention, in step (3), after the heat treatment is completed, the organic carbon source and hydrogen are turned off, and the mixture is cooled to room temperature under the protection of an inert atmosphere to prepare precursor 3.
[0037] According to an embodiment of the present invention, in step (3), the transition metal salt located on the surface of the precursor 2 is reduced to a metallic element under the action of hydrogen, namely a transition metal nanoparticle coating layer. The metallic element can act as a catalyst to catalyze the generation of carbon nanotubes or graphene on the surface of the transition metal nanoparticle coating layer from an organic carbon source, thereby forming nano-conductive carbon.
[0038] According to an embodiment of the present invention, in step (4), the mass ratio of the precursor 3 to the sulfur powder is 1:(1 to 3), for example, 1:1, 1:2 or 1:3.
[0039] According to an embodiment of the present invention, in step (4), the temperature of the heat treatment is 400–600°C, such as 400°C, 450°C, 500°C, 550°C, or 600°C. The heating rate is 2–10°C / min. The heat treatment time is 1–3 hours, such as 1 hour, 2 hours, or 3 hours. The inert atmosphere is, for example, nitrogen, helium, argon, etc.
[0040] According to an embodiment of the present invention, in step (4), the mass ratio of transition metal nanoparticles and transition metal sulfides in the composite anode material is controlled by controlling the content of sulfur powder. When the mass ratio of the precursor 3 to sulfur powder is 1:(1-3), the mass ratio of transition metal nanoparticles to transition metal sulfide nanoparticles in the obtained composite anode material is 1:(1-3).
[0041] The present invention also provides a transition metal sulfide / carbon composite anode material, which is prepared by the above method.
[0042] According to an embodiment of the present invention, the composite negative electrode material includes a core, a first coating layer covering the surface of the core, and a second coating layer covering the surface of the first coating layer;
[0043] The core is a nitrogen-doped porous amorphous carbon framework embedded with transition metal nanoparticles and transition metal sulfide nanoparticles; the first coating layer is transition metal sulfide nanoparticles; and the second coating layer is nano-conductive carbon.
[0044] According to an embodiment of the present invention, the nano-conductive carbon is a carbon nanotube or graphene.
[0045] According to an embodiment of the present invention, the transition metal nanoparticles are at least one of Cr nanoparticles, Fe nanoparticles, Co nanoparticles, Ni nanoparticles, and Cu nanoparticles.
[0046] According to an embodiment of the present invention, the transition metal sulfide nanoparticles are at least one of Cr2S3, Fe2S3, CoS2, NiS and CuS.
[0047] According to an embodiment of the present invention, the particle size of the core is 400-600nm, for example, 400nm, 450nm, 500nm, 550nm or 600nm.
[0048] According to an embodiment of the present invention, the thickness of the first coating layer is 10-20 nm, for example, 10 nm, 15 nm or 20 nm.
[0049] According to an embodiment of the present invention, the thickness of the second coating layer is 15-30 nm, for example, 15 nm, 20 nm, 25 nm or 30 nm.
[0050] According to an embodiment of the present invention, the mass ratio of the core to the first coating layer is 100:(1-10), for example, 100:1, 100:2, 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9 or 100:10.
[0051] According to an embodiment of the present invention, the mass ratio of the core and the second coating layer is 100:(5-10), for example, 100:5, 100:6, 100:7, 100:8, 100:9 or 100:10.
[0052] According to an embodiment of the present invention, in the core, the mass of transition metal nanoparticles and transition metal sulfide nanoparticles accounts for 40-48% (e.g., 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, or 48%) of the total mass of the core, the mass of nitrogen accounts for 8-12% (e.g., 8%, 9%, 10%, 11%, or 12%) of the total mass of the core, and the mass of carbon accounts for 40-52% (e.g., 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, or 52%) of the total mass of the core.
[0053] According to an embodiment of the present invention, in the composite negative electrode material, the mass ratio of transition metal nanoparticles to transition metal sulfide nanoparticles is 1:1 to 3, for example, 1:1, 1:2 or 1:3.
[0054] The present invention also provides the use of the above-mentioned transition metal sulfide / carbon composite anode material in anode sheets.
[0055] According to embodiments of the present invention, a negative electrode is used in an electrochemical device. Preferably, it is used as a negative electrode in a lithium-ion battery or a negative electrode in a sodium-ion battery.
[0056] The beneficial effects of this invention are:
[0057] This invention first generates a nitrogen-doped porous amorphous carbon framework embedded with transition metal nanoparticles by pyrolysis of transition metal organic framework materials at high temperature, which serves as the core material. Then, a transition metal salt is loaded on the surface of the core, forming a coating layer structure. This transition metal salt can form a transition metal nanoparticle coating layer under a hydrogen atmosphere. This transition metal nanoparticle coating layer acts as a catalyst, generating a nano-conductive carbon layer on the surface of the transition metal nanoparticle layer under the action of an organic carbon source. Finally, at high temperature, some of the transition metal nanoparticles react with sulfur powder to generate transition metal sulfide nanoparticles.
[0058] The in-situ synthesis method of this invention enhances the bonding force between transition metal sulfides, porous amorphous carbon framework, and nano-conductive carbon layers, making them a firmly bonded whole. The resulting composite anode material can withstand the stress caused by volume changes in the transition metal sulfides, constraining and buffering these changes, reducing the volume expansion factor of the transition metal sulfides after cyclic charging and discharging, and further preventing pulverization of the composite anode material. Simultaneously, it improves the conductivity and electrochemical performance of the composite anode material. Furthermore, the porous structure of the porous amorphous carbon and the conductivity of the nano-conductive carbon in the composite anode material shorten the path for lithium ions to intercalate into the metal sulfides, significantly increasing the ion exchange rate of the composite anode material and improving the fast-charging performance of the battery. Detailed Implementation
[0059] The present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention.
[0060] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0061] Example 1
[0062] (1) 10g Co(NO3)2·6H2O, 30g dimethylimidazole and 2000mL methanol were mixed and stirred at room temperature for 12 hours. After centrifugation and washing, the mixture was dried under vacuum at 100℃ to obtain Co-MOF.
[0063] (2) Place 15g of Co-MOF from step (1) into a high-temperature furnace, introduce nitrogen gas, heat at a rate of 10℃ / min until the temperature reaches 780℃, hold for 3 hours, and then cool to room temperature to obtain precursor 1.
[0064] (3) Mix 15g of precursor 1 from step (2) with 0.5L Co(NO3)2·6H2O aqueous solution (2g / L), stir for 12 hours, centrifuge and wash, and dry under vacuum at 70℃ to obtain precursor 2;
[0065] (4) Place 10g of precursor 2 from step (3) into a high-temperature furnace, introduce nitrogen (150mL / min) and hydrogen (150mL / min), heat at a rate of 10℃ / min until the temperature reaches 800℃, hold for 1.5 hours, then introduce acetylene at a flow rate of 30mL / min for 4 hours for chemical vapor deposition. After the reaction is complete, turn off the acetylene and hydrogen, and then cool to room temperature to obtain precursor 3.
[0066] (5) After mixing 1g of precursor 3 from step (4) with 1g of S powder, put it into a high-temperature furnace, introduce nitrogen gas, heat it at a rate of 10℃ / min until the temperature reaches 500℃, keep it at the temperature for 1 hour, and then cool it to room temperature to obtain the composite negative electrode material.
[0067] The composite anode material includes a core, a first coating layer covering the surface of the core, and a second coating layer covering the surface of the first coating layer; the core is a nitrogen-doped porous amorphous carbon framework embedded with transition metal Co nanoparticles and transition metal sulfide CoS2 nanoparticles; the first coating layer is transition metal sulfide CoS2 nanoparticles; and the second coating layer is carbon nanotubes.
[0068] In the composite anode material, the mass ratio of transition metal nanoparticles to transition metal sulfide nanoparticles is 1:1.2. The particle size of the core is 450 nm, the thickness of the first coating layer is 12 nm, and the thickness of the second coating layer is 18 nm. The mass ratio of the core to the first coating layer to the second coating layer is 100:4:6. In the core, the mass of transition metal nanoparticles and transition metal sulfide nanoparticles accounts for 40% of the total mass of the core, and the mass of nitrogen accounts for 12% of the total mass of the core.
[0069] Example 2
[0070] (1) 10g Cu(NO3)2·6H2O, 20g dimethylimidazole and 1200ml LDMF were mixed and stirred at room temperature for 8 hours. After centrifugation and washing, the mixture was dried under vacuum at 80℃ to obtain Cu-MOF.
[0071] (2) Place 10g Cu-MOF from step (1) into a high-temperature furnace, introduce nitrogen gas, heat at a rate of 6℃ / min until the temperature reaches 850℃, hold for 2 hours, and then cool to room temperature to obtain precursor 1.
[0072] (3) Mix 10g of precursor 1 from step (2) with 0.5L Cu(NO3)2·6H2O aqueous solution (2g / L), stir for 10 hours, centrifuge and wash, and dry under vacuum at 100℃ to obtain precursor 2;
[0073] (4) Place 10g of precursor 2 from step (3) into a high-temperature furnace, introduce nitrogen (120mL / min) and hydrogen (80mL / min), heat at a rate of 10℃ / min until the temperature reaches 850℃, hold for 1.5 hours, then introduce methane at a flow rate of 50mL / min for 6 hours for chemical vapor deposition. After the reaction is complete, turn off the methane and hydrogen, and then cool to room temperature to obtain precursor 3.
[0074] (5) After mixing 1g of precursor 3 and 2g of S powder from step (4), put them into a high-temperature furnace, introduce nitrogen gas, heat up at a rate of 5℃ / min until the temperature reaches 500℃, keep warm for 2 hours, and then cool to room temperature to obtain composite anode material.
[0075] The composite anode material includes a core, a first coating layer covering the surface of the core, and a second coating layer covering the surface of the first coating layer; the core is a nitrogen-doped porous amorphous carbon framework embedded with transition metal Cu nanoparticles and transition metal sulfide CuS nanoparticles; the first coating layer is transition metal sulfide CuS nanoparticles; and the second coating layer is carbon nanotubes.
[0076] In the composite anode material, the mass ratio of transition metal nanoparticles to transition metal sulfide nanoparticles is 1:2. The particle size of the core is 520 nm, the thickness of the first coating layer is 14 nm, and the thickness of the second coating layer is 20 nm. The mass ratio of the core to the first coating layer to the second coating layer is 100:6:8. In the core, the mass of transition metal nanoparticles and transition metal sulfide nanoparticles accounts for 46% of the total mass of the core, and the mass of nitrogen accounts for 10% of the total mass of the core.
[0077] Example 3
[0078] (1) 10g Fe(NO3)2·6H2O, 30g dimethylimidazole and 2000mL methanol were mixed and stirred at room temperature for 12 hours. After centrifugation and washing, the mixture was dried under vacuum at 100℃ to obtain Fe-MOF.
[0079] (2) Place 10g of Fe-MOF from step (1) into a high-temperature furnace, introduce nitrogen gas, heat at a rate of 10℃ / min until the temperature reaches 850℃, hold for 3 hours, and then cool to room temperature to obtain precursor 1.
[0080] (3) Mix 15g of precursor 1 from step (2) with 0.5L Fe(NO3)2·6H2O aqueous solution (2g / L), stir for 10 hours, centrifuge and wash, and dry under vacuum at 90℃ to obtain precursor 2;
[0081] (4) Place 10g of precursor 2 from step (3) into a high-temperature furnace, introduce nitrogen (150mL / min) and hydrogen (150mL / min), heat at a rate of 10℃ / min until the temperature reaches 800℃, hold for 1.5 hours, then introduce propane at a flow rate of 40mL / min for 5 hours for chemical vapor deposition. After the reaction is complete, turn off propane and hydrogen, and then cool to room temperature to obtain precursor 3.
[0082] (5) After mixing 1g of precursor 3 and 3g of S powder from step (4), put them into a high-temperature furnace, introduce nitrogen gas, and heat them at a rate of 6℃ / min until the temperature reaches 500℃. After holding the temperature for 3 hours, cool them to room temperature to obtain the composite negative electrode material.
[0083] The composite anode material includes a core, a first coating layer covering the surface of the core, and a second coating layer covering the surface of the first coating layer; the core is a nitrogen-doped porous amorphous carbon framework embedded with transition metal Fe nanoparticles and transition metal sulfide Fe2S3 nanoparticles; the first coating layer is transition metal sulfide Fe2S3 nanoparticles; and the second coating layer is carbon nanotubes.
[0084] In the composite anode material, the mass ratio of transition metal nanoparticles to transition metal sulfide nanoparticles is 1:3. The particle size of the core is 560 nm. The thickness of the first coating layer is 16 nm, and the thickness of the second coating layer is 25 nm. The mass ratio of the core to the first coating layer to the second coating layer is 100:8:10. In the core, the mass of transition metal nanoparticles and transition metal sulfide nanoparticles accounts for 48% of the total mass of the core, and the mass of nitrogen accounts for 8% of the total mass of the core.
[0085] Comparative Example 1
[0086] (1) 10g Co(NO3)2·6H2O, 30g dimethylimidazole and 2000mL methanol were mixed and stirred at room temperature for 12 hours. After centrifugation and washing, the mixture was dried under vacuum at 100℃ to obtain Co-MOF.
[0087] (2) Place 15g of Co-MOF from step (1) into a high-temperature furnace, introduce nitrogen gas, heat at a rate of 10℃ / min until the temperature reaches 780℃, hold for 3 hours, and then cool to room temperature to obtain precursor 1.
[0088] (3) After mixing 1g of precursor 1 from step (2) with 1g of S powder, put it into a high-temperature furnace, introduce nitrogen gas, heat it at a rate of 10℃ / min until the temperature reaches 500℃, keep it at the temperature for 1 hour, and then cool it to room temperature to obtain the composite negative electrode material.
[0089] The composite anode material is a nitrogen-doped porous amorphous carbon framework embedded with transition metal Co nanoparticles and transition metal sulfide CoS2 nanoparticles.
[0090] In the composite anode material, the mass ratio of transition metal nanoparticles to transition metal sulfide nanoparticles is 1:1.2, the particle size of the core is 450 nm, the mass of transition metal nanoparticles and transition metal sulfide nanoparticles accounts for 40% of the total mass of the core, and the mass of nitrogen accounts for 12% of the total mass of the core.
[0091] Electrochemical performance testing:
[0092] Half-cell testing method: The composite negative electrode material prepared in Examples 1-3 and Comparative Example 1 was mixed evenly with conductive carbon black (SP): carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) in a ratio of 95:1:1.5:2.5 (mass ratio). The mixture was then coated onto copper foil, and the coated electrode was dried in a vacuum drying oven at 120°C for 12 hours. Simulated battery assembly was performed in an argon-protected Braun glove box. The electrolyte was 1M-LiPF6+EC:DEC:DMC (volume ratio 1:1:1), and lithium metal sheet was used as the counter electrode. Simulated battery testing was conducted in a 5V, 10mA Xinwei battery test cabinet with a charge / discharge voltage of 0.01-1.5V and a charge / discharge rate of 0.1C. The first-week charge capacity and first-week coulombic efficiency obtained from the tests are listed in Table 1.
[0093] Full cell testing method: Using the composite negative electrode materials prepared in Examples 1-3 and Comparative Example 1 as negative electrodes, lithium cobalt oxide as positive electrodes, and 1M-LiPF6+EC:DEC:DMC (volume ratio 1:1:1) solution as electrolyte, full cells were assembled. They were charged and discharged at room temperature at rates of 0.1C and 0.5C, with a voltage range of 3.0-4.2V. The cycle performance obtained is listed in Table 1.
[0094] Table 1. Electrochemical performance test results
[0095]
[0096] The embodiments of the present invention have been described above. However, the present invention is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a transition metal sulfide / carbon composite anode material, the method comprising the following steps: (1) The transition metal-organic framework material is heat-treated under the protection of an inert atmosphere to prepare the precursor 1; the precursor 1 has a nitrogen-doped porous amorphous carbon skeleton structure, and the nitrogen-doped porous amorphous carbon skeleton is also embedded with transition metal nanoparticles. (2) The precursor 1 from step (1) is mixed with an aqueous solution of a transition metal salt and stirred to prepare the precursor 2; the transition metal salt loaded onto the surface of the precursor 1 forms a coating layer structure, which is the precursor 2. (3) The precursor 2 in step (2) is heat-treated under the protection of hydrogen and an inert atmosphere, and then an organic carbon source is introduced to continue the heat treatment to prepare the precursor 3. The transition metal salt on the surface of the precursor 2 is reduced to a metal element under the action of hydrogen, namely the transition metal nanoparticle coating layer. The metal element acts as a catalyst to catalyze the organic carbon source to generate carbon nanotubes or graphene on the surface of the transition metal nanoparticle coating layer. (4) The precursor 3 from step (3) is mixed with sulfur powder and heat-treated under an inert atmosphere to prepare the transition metal sulfide / carbon composite anode material. The composite anode material includes a core, a first coating layer covering the surface of the core, and a second coating layer covering the surface of the first coating layer; the core is a nitrogen-doped porous amorphous carbon framework embedded with transition metal nanoparticles and transition metal sulfide nanoparticles; the first coating layer is transition metal sulfide nanoparticles; and the second coating layer is nano-conductive carbon.
2. The preparation method according to claim 1, wherein, In step (1), the transition metal-organic framework material is prepared by the following method: mixing transition metal salt, organic ligand and organic solvent, reacting, and preparing the transition metal-organic framework material.
3. The preparation method according to claim 2, wherein, The transition metal salt is selected from at least one of chromium salts, iron salts, cobalt salts, nickel salts, and copper salts; And / or, the organic ligand is selected from at least one of naphthalenetetracarboxylic anhydride, dimethylimidazole, 2,5-dihydroxyterephthalic acid, pyromellitic acid, and terephthalic acid; And / or, the organic solvent is selected from at least one of methanol, ethanol, formaldehyde, acetaldehyde, DMF and water.
4. The preparation method according to claim 2, wherein, The mass ratio of the transition metal salt to the organic ligand is 1:(2~4); And / or, the sum of the masses of the transition metal salt and the organic ligand, in volume ratio to the organic solvent, is (0.01~0.1) g: 1 mL.
5. The preparation method according to claim 1, wherein, In step (1), the temperature of the heat treatment is 700~900℃, and the time of the heat treatment is 1~3 hours; And / or, in step (2), the mass ratio of the transition metal salt to precursor 1 is 1:(10~20); And / or, in step (2), the transition metal salt is selected from at least one of chromium salt, iron salt, cobalt salt, nickel salt and copper salt.
6. The preparation method according to any one of claims 1-5, wherein, In step (3), the volume ratio of hydrogen to inert atmosphere is 1:(1-3). And / or, in step (3), the temperature of the heat treatment is 700~900℃; And / or, step (3) specifically includes the following steps: Precursor 2 from step (2) was heated to 700-900°C for 1-3 hours under the protection of hydrogen and an inert atmosphere. Then, an organic carbon source was introduced and kept at the temperature for 1-5 hours. After cooling to room temperature, precursor 3 was obtained. And / or, in step (3), the organic carbon source is selected from one or more of acetylene, ethylene, methane, ethane, propane and n-butane; And / or, in step (3), the volume ratio of the organic carbon source to the inert atmosphere is 1:(2~15); And / or, in step (3), an organic carbon source is introduced into each gram of precursor 2 at a rate of 3-5 mL / min.
7. The preparation method according to any one of claims 1-5, wherein, In step (4), the mass ratio of the precursor 3 to sulfur powder is 1:(1~3); And / or, in step (4), the temperature of the heat treatment is 400~600℃ and the time of the heat treatment is 1~3 hours.
8. A transition metal sulfide / carbon composite anode material, which is prepared by the method described in any one of claims 1-7.
9. The transition metal sulfide / carbon composite anode material according to claim 8, wherein, The composite anode material includes a core, a first coating layer covering the surface of the core, and a second coating layer covering the surface of the first coating layer. The core is a nitrogen-doped porous amorphous carbon framework embedded with transition metal nanoparticles and transition metal sulfide nanoparticles; the first coating layer is transition metal sulfide nanoparticles; and the second coating layer is nano-conductive carbon.
10. The transition metal sulfide / carbon composite anode material according to claim 9, wherein, The conductive carbon nanotubes are carbon nanotubes or graphene. And / or, the transition metal nanoparticles are at least one of metal Cr nanoparticles, metal Fe nanoparticles, metal Co nanoparticles, metal Ni nanoparticles and metal Cu nanoparticles; And / or, the transition metal sulfide nanoparticles are at least one of Cr2S3, Fe2S3, CoS2, NiS and CuS.
11. The transition metal sulfide / carbon composite anode material according to claim 9, wherein, The particle size of the core is 400-600 nm; And / or, the thickness of the first coating layer is 10-20 nm; And / or, the thickness of the second coating layer is 15-30 nm; And / or, the mass ratio of the core to the first cladding layer is 100:(1-10); And / or, the mass ratio of the core and the second coating layer is 100:(5-10); And / or, in the core, the mass of transition metal nanoparticles and transition metal sulfide nanoparticles accounts for 40-48% of the total mass of the core, the mass of nitrogen accounts for 8-12% of the total mass of the core, and the mass of carbon accounts for 40-52% of the total mass of the core; And / or, in the composite anode material, the mass ratio of transition metal nanoparticles to transition metal sulfide nanoparticles is 1:1~3.
12. Use of the transition metal sulfide / carbon composite anode material according to any one of claims 8-11, wherein it is used in an anode sheet.
Citation Information
Patent Citations
Amorphous carbon coated metal sulfide and preparation method thereof
CN110534739A
Carbon-assembled zinc sulfide hollow nano polyhedral honeycomb material as well as preparation and application thereof
CN112366312A
Method for fabricating modified-silicon-based negative-electrode material by vapor deposition
WO2017008615A1